Analysis of Digital Marketing Processes to Improve Business Performance: Foods and Beverages MSMEs in Indonesia - Elvita Laurensia Santoso; Walda Vivian; Sekar Wulan Prasetyaningtyas (Journal of Social Science, 2022)
In this era, the way people do business has switched to digital marketing. Accordingly, the purpose of this research is to find out the right digital marketing processes to improve business performance, with a focus on foods and beverages MSMEs in Semarang, Indonesia, motivated by the growth of digital marketing implemented by business owners. This research paper is based on a qualitative approach with a descriptive research method and used literature review, interviews, and observation to collect the data. This research examines the digital marketing processes of foods and beverages MSMEs in Semarang, which has rarely been focused on, and reveals that MSMEs that carried out more complete digital marketing processes have the potential to improve business performance